Composition, structure and formation factors of macroinvertebrate communities in low-mountain lakes of the Russian Altai - Dmitry M. Bezmaternykh; Olga N. Vdovina (Acta Biologica Sibirica, 2023)
Recent data suggests a significant difference in physical and biological properties between low-mountain lakes and high-mountain or lowland water bodies. However, the taxonomic composition and structure of bottom invertebrates in low-mountain lakes of Altai remain unknown. Due to climate change and growing anthropogenic impact, studying the composition and structure of macrozoobenthos in these lakes is becoming increasingly urgent. In 2022, a study was conducted on macrozoobenthos from foothill lakes of the Russian Altai, specifically Kireevo in the Krasnogorsk region, Aya (Aiskoye) in the Altai region, Koksha and Svetloye in the Soviet region, Kolyvanskoye in the Zmeinogorsk region, and Beloye in the Kuryinsky region of Altai Krai. The study identified 152 species from 9 classes, including Turbellaria (1), Nematoda (1), Oligochaeta (17), Hirudinea (5), Bivalvia (2), Gastropoda (8), Arachnida (10), Crustacea (2), and Insecta (106). Of the insects, the order Diptera (69 species, including 59 chironomids) had the greatest species diversity. Additionally, the orders Trichoptera (16), Coleoptera (7), Ephemeroptera (5), Odonata (4), Heteroptera (4), and Megaloptera (1) were identified. Most of the studied lakes in the Russian Altai (Aya, Beloye, Kireevo, and Kolyvanskoye) had a taxonomic composition of macrozoobenthos similar to lowland lakes. Two lakes (Koksha and Svetloye) had a combination of features from both lowland and high-mountain lakes. The content of organic substances and their decomposition products in water, as well as substrate type, were the most significant factors determining the development of macroinvertebrate communities in the studied lakes.